2022
DOI: 10.1021/acscatal.2c04894
|View full text |Cite
|
Sign up to set email alerts
|

Corrugation-Induced Active Sites on Pristine Graphene for H2 Activation

Abstract: Pristine graphene is widely considered to be chemically inert, but recent experimental studies have suggested that it can provide frustrated Lewis pairs (FLPs) for activating H 2 under mild conditions. Using density functional theory (DFT) and ab initio molecular dynamics (AIMD) calculations, we explore in this work the possibility that corrugation in pristine graphene is responsible for the formation of FLPs and thus its observed catalytic activity. Our DFT results demonstrate that the ease of H 2 activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…On the other hand, the presence of convex ripples with considerable curvature t/D makes the dissociation reaction energetically favourable [Fig. 2(a)], in agreement with recent simulations [11,16,36]. For example, if we consider a graphene ripple with curvature t/D = 12%, the dissociation of molecular hydrogen on the central positions [inset of Fig.…”
Section: B Dissociation Of Hydrogen Moleculessupporting
confidence: 85%
“…On the other hand, the presence of convex ripples with considerable curvature t/D makes the dissociation reaction energetically favourable [Fig. 2(a)], in agreement with recent simulations [11,16,36]. For example, if we consider a graphene ripple with curvature t/D = 12%, the dissociation of molecular hydrogen on the central positions [inset of Fig.…”
Section: B Dissociation Of Hydrogen Moleculessupporting
confidence: 85%
“…Among these FLPs, the N···B­(CF 3 ) 2 FLPs is the most active catalyst for H 2 dissociation. Importantly, the activity of the designed FLPs for H 2 dissociation is higher than other heterogeneous FLPs with metal-free active centers ,,,,, and even comparable to homogeneous FLPs . Therefore, the designing strategy of these FLPs is of great use for developing novel effective heterogeneous FLPs on metal-free materials.…”
Section: Resultsmentioning
confidence: 98%
“…Primo et al reported that FLPs account for the high activity of graphene materials for the selective hydrogenation of acetylene and alkene . Recently, Wan et al claimed that the FLPs in Primo’s experiments could be attributed to the corrugation in realistic graphene materials, which exhibits catalytic activities proportional to the degree of corrugation for heterolytic H 2 cleavage . Su et al reported that FLPs can also be constructed on bilayer graphene and graphene ribbons by co-doping electron-deficient boron (B, the acid site) and electron-rich nitrogen (N, the base site) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Semi-immobilized FLPs represent an initial endeavor in this direction, with either of the Lewis pairs doped into the solid supports. However, they are less than ideal for practical applications in terms of material synthesis and catalyst separation. Recently, pioneer researches have revealed the fully immobilized FLP catalysts based on carbonaceous materials, hexagonal boron (carbon) nitride (h-BN, BCN), and alkylammoniotrifluoroborate-functionalized polystyrene derivatives for H 2 or C–H bond activation. Unfortunately, some of the above systems still suffered from several limitations, such as high H 2 pressure, limited substrate scope, which emphasized the difficulty in fabricating an efficient heterogeneous FLP catalyst with electron and steric hindrance preciously tailored.…”
Section: Introductionmentioning
confidence: 99%